THE COMPARISON OF USING STAD AND JIGSAW TECHNIQUE OF COOPERATIVE LEARNING METHOD TOWARD STUDENTS’ SPEAKING ABILITY OF SMP N 4 METRO ACADEMIC YEAR 2011/2012 - Suko Suko (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2012)
Many techniques presented as a solution in this research to develop speaking ability, they are STAD and Jigsaw technique. In this research, the researcher uses the experiment design. The research is conducted at the eight levels of SMP N 4 Metro in the academic year 2011/ 2012. The researcher takes 46 students as the sample, 23 students are as experiment class and 23 students are as control class that taken based on cluster random sampling. After analyzing the data by using the formula of ttest, the researcher get the result of ttest is 3,95 and ttable is 2,69 (on criterion 1) and 2,01 (on criterion 2). It means that thit > ttable. And the criterion of ttest is Ha accepted if thit> ttable. So, There is significant difference between using STAD and Jigsaw technique toward students’ speaking ability for the eight grades students of SMPN 4 Metro and STAD technique is more effective than Jigsaw tecnique toward students’ speaking ability for the eight gradea students of SMPN 4 Metro.Cooperative Learning Method, STAD, Jigsaw and Students Speaking Ability